L’éloquence de la suavitas : Richard Crashaw et la spiritualité salésienne - Vincent Roger (Etudes Epistémè)
This essay aims to examine a certain number of affinities that can be found between Richard Crashaw’s poetry and the works of Francis de Sales. A network of biographical, spiritual as well as literary likenesses unites the authors’ worlds. The “Doctor of Divine Love”’s affective theology perfectly illuminates the poet’s universe and may partly account for the emphasis on sweetness in his divine eloquence.